2022
DOI: 10.1016/j.devcel.2021.11.025
|View full text |Cite
|
Sign up to set email alerts
|

piRNAs initiate transcriptional silencing of spermatogenic genes during C. elegans germline development

Abstract: Summary Eukaryotic genomes harbor invading transposable elements that are silenced by PIWI-interacting RNAs (piRNAs) to maintain genome integrity in animal germ cells. However, whether piRNAs also regulate endogenous gene expression programs remains unclear. Here, we show that C. elegans piRNAs trigger the transcriptional silencing of hundreds of spermatogenic genes during spermatogenesis, promoting sperm differentiation and function. This silencing signal requires piRNA-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 75 publications
5
26
1
Order By: Relevance
“…This result is consistent with the model that piRNA targeting induces the production of 22G-RNAs which are then loaded into WAGO-1 and HRDE-1 (Lee et al, 2012;Cornes et al, 2022). Our complete analysis reveals that PPW-1 and PPW-2 also work within the context of PRG-1 targeting.…”
Section: Hierarchy and Interconnected Regulation Of Multiple Srna Pat...supporting
confidence: 90%
“…This result is consistent with the model that piRNA targeting induces the production of 22G-RNAs which are then loaded into WAGO-1 and HRDE-1 (Lee et al, 2012;Cornes et al, 2022). Our complete analysis reveals that PPW-1 and PPW-2 also work within the context of PRG-1 targeting.…”
Section: Hierarchy and Interconnected Regulation Of Multiple Srna Pat...supporting
confidence: 90%
“…3 E).This subpackage further permits us to perform localization of RNAs with subpixel accuracy by using a Gaussian fitting ( Mueller et al 2013 ). Lastly, we provide the possibility to perform a colocalization analysis between spot detection performed in multiple channels ( Cornes et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our analyses indicate that CSR-1 binding at various locations in a transcript can result in the protection of the entire transcript from piRNA recognition (Figure 6). Indeed, a recent report has shown that tethering of CSR-1 to a single locus at the 3’ UTR of an endogenous mRNA can protect that mRNA from piRNA silencing (34). In addition, our analyses reveal that CSR-1 targeted regions are locally protected against WAGO 22G-RNA production (Figure 6).…”
Section: Discussionmentioning
confidence: 99%